Effect of Bio-Stimulant Concentrations on Growth and Yield of Peanut (Arachis hypogaea) in the Philippines - Sanglap, Yna Marie L.; Fernandez, Josie Faye L.; Oñal, Paulino Miguel M.; Oñal, Jr., Paulino A. (Future Science / FSH-PH Publications, 2025)
The study sought to determine the effects of different levels of concentrations of bio-stimulant solution (BSS) in improving the growth and yield performance of peanut plant. The study was conducted at UNO-R, Inc, Philippines last February to June 2024. Biyaya variety was used as planting material. The study was layout in RCBD (Randomized Complete Block Design) with 4 treatments, and replicated 4 times. BSS was diluted in water and applied 6 inches from the base of each plant. Statistical analysis revealed highly significant differences among treatments in growth parameters such as germination period and flower initiation, plant height, weight of stems and leaves, and biomass. For the period of germination, highest plant height, weight of stems and leaves, biomass, and period of flowering they were obtained from plants applied with 15%, followed by 10%, and 5% BSS (ɑ =0.01), respectively. On the other hand, untreated plants have the longest days of germination, shortest height, lightest weight of stem and leaves, as well as the biomass, and late in flower initiation.This study recommends the application of 15% BSS for optimal peanut growth and yield.